A polyimide/poly(N-vinylimidazole) membrane for CO2/CH4 separation with high selectivity and permeability. (September 2022) - Yan, Shuo; Yu, Haibin; Chen, Zan
Membranes with both good permeation and selectivity are highly desired for gas separations. In this study, we synthesized a new 6FDA-type polyimide copolymer 6FDA-BDTA-ODA, and then an organic polymer of poly ( N -vinylimidazole) was doped into the polyimide to prepare mixed matrix membranes (MMMs). We also studied the effect of poly ( N -vinylimidazole) contents on the separation performance of MMMs. The results showed that the ideal selectivity for CO2 /CH4 was improved by adding the poly ( N -vinylimidazole) filler. The ideal selectivity reached 63.5 with 6 wt% poly ( N -vinylimidazole) loading with the permeability of 29.2 Barrer. The highly permeable MMMs showed a considerably enhanced performance for CO2 /CH4 that close to the 2008 Robeson upper-bound. The gas separation performance of the prepared MMMs for CO2 /CH4 was improved compared to that of the pure polymer membrane, indicating that the copolyimide/poly ( N -vinylimidazole) MMMs have promising applications in CO2 /CH4 gas separation.